Integrasi pandangan islam dan biologi dalam menjaga kesehatan manusia serta implikasinya terhadap hukum fiqih kontemporer - Ilmiyah, Alifa (Maliki Interdisciplinary Journal, 2026)
Health is a very important aspect in Islamic teachings. Islam views health not only as a gift, but also as a responsibility that must be maintained and cared for. From a biological perspective, human health is greatly influenced by various biological processes such as metabolism, the immune system, and hormonal balance, all of which reflect how complex and perfect Allah SWT’s creation is. This article aims to link the Islamic perspective with biological concepts in an effort to maintain human health, while also examining the influence of modern biological developments on Islamic jurisprudence laws, especially in the medical context. Technological advances such as organ transplantation, vaccination, and genetic engineering require the renewal of Islamic law through ijtihad based on maqashid sharia and scientific principles. This study uses a qualitative descriptive method with a literature study approach to classical and contemporary Islamic sources, as well as modern biological literature. The results of the study show that there is a meeting point between Islam and biology in terms of the urgency of maintaining health as part of worship, as well as the need for an adaptive Islamic legal response to the dynamics of ever-evolving science.